Hessenhuis : 'G 58 - 85' : Catalogus. - Verbraeken, Paul (Antwerpen : L. Denys, Educatieve Dienst van de Musea, 1985)
Ausloos, Paul ; Bervoets, Pol ; Bogaert, André ; Claus, Mark ; De Leeuw, Bert ; De Meyer, Lutgart ; Denkens, Herman ; Dries, Jan ; Estercam, Vic ; Ganzevoort, Wybrand ; Gentils, Vic ; Graafmans, Daan ; Kersting, Jef ; Leblanc, Walter ; Mara, Pol ; Overberghe, Cel ; Philippi, Frank ; Servaes, Louise ; Strijbosch, Jan ; Tas, Filip ; Van Breedam, Camiel ; Van De Velde, Wim ; Vanermen, Walter ; Van Hoeydonck, Paul ; Van Roost, Maurice ; Van Severen, Dan
Hessenhuis. 'G 58 - 85', Hessenhuis, Antwerpen, 13 december 1985 - 16 maart 1986
boek